GROUPINGS OF POPULATION I OBJECTS IN THE GALAXY - Berdnikov, L. N.; Efremov, Yu. N.; Glushkova, E. V.; Turner, D. G. (Одеські астрономічні публікації, 2017)
The distribution of Cepheids in the Galaxy is studied using a new catalogue of Cepheid distances in conjunction with the method of hierarchical clustering. The resulting delineation of Cepheid complexes is compared with those for other Population I objects: open clusters and OB-associations. Parameters derived for complexes of Cepheids are very similar to those for open clusters and OB-associations: the typical dimension of first level groups is ∼0.2 kpc, while the size of complexes is ∼0.9 kpc. Mostly the complexes of different objects are spatially coincident, but not always.